Development and assessment of an innovative culturally sensitive educational videotape to improve adherence to highly active antiretroviral therapy in Soweto, South Africa. - Wong, Ilene Y; Lawrence, Nicholas V; Struthers, Helen; McIntyre, James; Friedland, Gerald H (Journal of acquired immune deficiency syndromes (1999), 2006)
The increasing availability of antiretroviral medication (ARV) therapy in the face of limited chronic medication-taking experience among resource-poor South Africans has raised concerns about adequate adherence to these medications. We hypothesized that a culturally sensitive audiovisual patient education program would be of substantial and measurable benefit in increasing patient understanding of the concepts of ARV resistance risk and medication-taking skills. To identify potential barriers to adherence and successful strategies to promote adherence, 6 focus groups with health care providers and HIV-positive adherence counselors were held, resulting in the production of a 17-minute culturally sensitive educational videotape. Basic drug-taking concepts and practical advice on how to improve adherence were presented in the videotape. Thirty-four HIV-positive patients (including 11 ARV-naive patients and 23 ARV-experienced patients) were shown the educational videotape, and their knowledge about medication taking was evaluated by a 24-point pre- and postvideotape questionnaire. On average, the 34 patients gained 2.2 knowledge points (P = 0.021). ARV-naive patients had an average improvement of 3.0 points (P = 0.0028), with most significant gains in the areas of understanding medication-taking strategies and side effects. These preliminary findings indicate that a culturally sensitive educational videotape can improve medication-taking knowledge in South Africa and that further study of the potential efficacy of using media technology to improve individuals' adherence to ARV therapy is warranted.
Keywords: Adolescent; Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Female; HIV Infections; Humans; Male; Middle Aged; Patient Compliance; Patient Education as Topic; South Africa; Videotape Recording